THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY LEVEL ON INTEREST IN CREATING MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) - Sri Rohayati; Tazkiyah 'Ainul Qolbi (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2022)
This study aims to determine the impact of Islamic financial literacy on the desire to start micro, small, and medium-sized businesses (MSMEs). Knowledge of Islamic finance is crucial for business actors, including MSMEs. Financial literacy in accordance with Islamic law is an extension of financial literacy. It indicates that as Islamic financial literacy increases, so does the desire to start a business. This study employed quantitative research methods involving regression, and SPSS.20 was used to analyze the data. This study's sample consisted of 45 Sharia Economics Study Program graduates at the Darussalam Institute of Islamic Studies, calculated using the Solvin formula. We are collecting data using a questionnaire. Results indicated that the level of Islamic financial literacy significantly impacted the desire to establish micro, small, and medium-sized businesses (MSMEs).